2016
DOI: 10.1007/s11356-016-7051-0
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Fe-reduced graphene oxide nanocomposite as an efficient catalyst for sulfamethazine degradation in aqueous solution

Abstract: A heterogeneous Fenton catalyst Ce(0)-Fe(0)-reduced graphene oxide (Ce-Fe-RGO) was synthesized with chemical reduction methods and used for degradation of sulfamethazine. The introduction of Ce and graphene increased the dispersibility of iron particles which was confirmed by SEM and TEM. The results of VSM analysis showed good magnetism of Ce-Fe-RGO. The catalyst performance was compared with other kinds of catalysts (Fe(0) and Ce(0)-Fe(0)) for degradation of sulfamethazine. The results showed that Ce(0)-Fe-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The lower TOC removal efficiency can be ascribed to that some intermediates produced in the system being difficult to further degrade by · OH. The intermediates of SMT degradation were studied previously by our group . Several intermediate products, including 4‐amino‐N‐carbamimidoyl‐benzenesulfanamide, sulfanilic acid, 2‐amino‐4,6‐dimethylpyrimidine, sulfanilamide, aniline and carboxylic acid were detected in the final solution by GC‐MS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower TOC removal efficiency can be ascribed to that some intermediates produced in the system being difficult to further degrade by · OH. The intermediates of SMT degradation were studied previously by our group . Several intermediate products, including 4‐amino‐N‐carbamimidoyl‐benzenesulfanamide, sulfanilic acid, 2‐amino‐4,6‐dimethylpyrimidine, sulfanilamide, aniline and carboxylic acid were detected in the final solution by GC‐MS.…”
Section: Resultsmentioning
confidence: 99%
“…The intermediates of SMT degradation were studied previously by our group. 18 CONCLUSIONS Fe 3 O 4 /Mn 3 O 4 composites were successfully synthesized with a polyol process and an impregnation method, which had excellent catalytic activity for the degradation of SMT in a heterogeneous Fenton-like process. Characterization of the catalyst before and after reaction indicated that the catalyst was stable.…”
Section: Ions Leaching and H 2 O 2 Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene possesses interesting physical and chemical properties, and has a wide range of technological applications in recent years [10][11][12]. In particular, great efforts have been devoted to exploring graphene oxide (GO) as novel antimicrobial agents with a severe cytotoxic effect on bacteria [13][14][15][16], fungi [17,18], and plant pathogens [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Cu, Mn, Fe oxides were used for CWAO processes: degradation of Acid Red over Cu-Mn/TiO2 composites [316], oxidation of Rhodamine B over MnO2 [317], oxidation of paper industry wastewater over Ce0.4Fe0.6O2 [318] or Ce1−xCoxOy mixed oxides [319]. CWPO were mainly performed over Fe [320,321] or Cu catalysts [322], the…”
Section: Wet Air Oxidationmentioning
confidence: 99%